Ayat Toleransi Dalam Al-qur’an; Tinjauan Tafsir Al-Qurthubi - Mufidatul Bariyah Bariyah (LPPM Institut Pesantren KH. Abdul Chalim, 2019)
Embodies the Attitude of religious tolerance in Indonesia is not by way of saying that all religions that exist in the community is the same, because in fact we can see, every religion is different, although it has some aspects in common. For example in the case of the core teachings that together teach kindness to its adherents. The tolerant attitude that must be applied in Indonesia is a necessity of society in accepting the existence of differences that is certainly on the everyday life with open arms. The reception of this kind is not a union arbitrarily to all religions, but as an effort to cultivate and develop an attitude of mutual acceptance in the form of respect for all the differences that exist in the community. According to the teachings of Islam, tolerance is not only in the middle against fellow human beings, but also against god's creation that other, better for the environment, the universe, and the beast, the manifestation of religious tolerance can be interpreted as an attitude of individuals or groups who accept the existence of differences arising from a belief to a different religion. Through the process of appreciating and accepting the existence of different faiths, but in these social relationships, not infrequently we find the presence of conflict as a parasite that hinder the realization of social normative, it is due to adannya goal difference in the life of each, either group or individual. See religion evolve into the impression that raises issues that are emotional shell so blind with understanding tolerance. Within the scope of the religion of Islam, Al-quran in outline has been talking about the relation of creatures with God along with the Universe and its contents, Al-quran, also examine about the discussion of humanitarian issues that confront him in this life.